JS01.4.A The neurocognitive function changes with awake craniotomy for low-grade glioma in the left hemispheric eloquent regions. (9th September 2021) - Wang, Y; Ji, P; Guo, S; Liu, J; Zhai, Y; Wang, N; Qu, Y; Wang, L
Abstract: BACKGROUND: Cognitive deficit was frequently observed in glioma patients, especially for those on the eloquent area. Considering the increased life expectancy, brain mapping during awake craniotomy was preferentially applied to exacerbate neurocognitive deficits. The aim of the current study was to evaluate the neurocognitive changes during the perioperative period of resection of low-grade glioma (LGG) in the left side eloquent area with awake craniotomy in a major neurosurgical center in China for 5 years. MATERIAL AND METHODS: We retrospectively analyzed patients with left-sided glioma in eloquent areas, who received awake craniotomy during 2016–2020. Montreal Cognitive Assessment Scale, BN-20, and EORTC-QLQ-C30 questionnaire were applied for neurological cognitive assessment. We performed a correlation analysis between changes in cognitive performance and tumor characteristics, including tumor location, pathological grade. Treatment-related factors were also analyzed, such as the extent of resection (EOR), preoperative and postoperative Karnofsky Performance Score (KPS), postoperative treatment strategy (chemo- and radiotherapy), progression-free survival (PFS), overall survival (OS). RESULTS: 68 patients were included in our current study. For the language domain, memory domain, and executive functions, 7.4% (5/68) patients presented mild postoperative cognitive performance deterioration compared to preoperative. Tumor location was the only factor that greatly influenced the postoperative cognitive performance, while other features (EOR, KPS, pathological grades) and treatment strategy were found no effect on cognitive change. The extent of tumor resection ranged from 81% to 100%. CONCLUSION: Our study underlines the importance of the application of brain mapping during awake craniotomy, which helps to maximize extent of tumor resection while preserving cognitive function in individuals with LGG in eloquent regions.